Study the Optical Properties of Iron- Free Magnetic Lens - Abdulla, Roaa T (Al-Nahrain Journal of Science, 2018)
Attention has been concentrated on the effect of the current density and lens dimensions on iron-free magnetic lens design. A magnetic field has been calculated for a such magnetic lens for different values of current density. Also, the radial and spiral distortion aberration coefficients have been computed. Results have clearly shown that the low aberration coefficients can get at current density of high value and the ratio S/D of the system within the rang 0.5 ≤ S/D ≤ 2.